AWS certified developer associate : a practical guide - Martinez, Matthew (Packt Publishing, 2019)
"The purpose of this course is to teach you AWS practically so that you can take and pass the test easily. All the crucial parts of the AWS Developer Associate certification are included in the course. Each chapter has its own practical use cases, and there will never be a moment where you feel lost. You will learn about AWS basics, EC2, S3, Cloud Formation, DynamoDB, VPC, IAM, lambdas, and lot more. Students should have access to an AWS account to practice in the concepts and basic knowledge of Linux will be useful for completing this course."--Resource description page